The petrography, metamorphism and deformation history of Neoproterozoic rock from Gida Ayana, Western Ethiopia: implication of tectonometamorphic evolution - Mihret, Bishaw; Wuletaw, Ajebush (Frontiers in Earth Science, 2025)
The geological study of basement rocks in the Gida Ayana area of western Ethiopia has revealed significant findings regarding the local petrography, metamorphism, and deformation history. The geological evolution of rocks in the area has been analyzed thoroughly through detailed field investigations, overprinting and cross-cutting relationships, and petrographic studies of metamorphic rocks. The findings reveal that the study area experienced polyphase deformations, with at least three ductile deformation phases (D1 to D3) associated with two metamorphic events (M1 and M2), and development of brittle structures such as irregular fractures, joints, and veins. Each type of structure observed in the study area has been discussed in detail, highlighting the formation of F2 folds, S2 foliations, L2 lineations, S3 foliations, F3 folds, and joints. The development of a steep northeast-to-southwest striking foliation S2 gneissic banding and mineral assemblage (Or + Pl + Qtz + Bt + - Sp) indicate that the prograde metamorphism (M1) is synchronous with D2 phase. The alteration products sericite, chlorite, and biotite indicate a retrograde metamorphism (M2) that may have occurred during uplift or D3 shear-zone-related fluid migrations. The regional tectonic setting of Gida Ayana is within the East African Orogen. The relationships between the Gida Ayana metamorphism and deformations with larger tectonic processes, such as continental collisions during the pan-African Orogeny, were discovered. We also analyzed the orientation and features of the deformation structures as well as their associated metamorphic events to offer important insights into the tectonic and metamorphic history of the East African Orogen.